Employing intermediaries to achieve freshwater quality improvements: lessons from catchment groups in Aotearoa New Zealand. Issue 1 (2nd January 2022) - Kirk, Nicholas; Robson-Williams, Melissa; Fenemor, Andrew; Heath, Nathan
ABSTRACT: Intermediaries are actors who assist with sustainability transitions. Intermediaries connect, translate, and facilitate flows of information between different groups by positioning themselves between these groups. In this paper we focus on the roles of freshwater intermediaries who have been employed by local authorities and ask how these intermediaries help communities achieve freshwater quality improvements. To answer this question, we present three case studies of freshwater intermediaries working to improve freshwater quality in the Hawke's Bay region of Aotearoa New Zealand (NZ). Our results suggest that intermediaries can help communities improve freshwater quality if they are given the time and resources to establish long-term relationships with communities, and if they are able to synchronise freshwater intermediary work with regional and national freshwater policy objectives. We conclude by arguing that freshwater intermediary work has been undervalued in NZ land and water management, resulting in local and central government attempting to resolve freshwater quality concerns through increasingly prescriptive and complex policy in regulations. Some specific lessons for use of freshwater intermediaries in New Zealand conclude the paper.